2022
DOI: 10.3390/biology11121855
|View full text |Cite
|
Sign up to set email alerts
|

Soil Geochemical Properties Influencing the Diversity of Bacteria and Archaea in Soils of the Kitezh Lake Area, Antarctica

Abstract: It is believed that polar regions are influenced by global warming more significantly, and because polar regions are less affected by human activities, they have certain reference values for future predictions. This study aimed to investigate the effects of climate warming on soil microbial communities in lake areas, taking Kitezh Lake, Antarctica as the research area. Below-peak soil, intertidal soil, and sediment were taken at the sampling sites, and we hypothesized that the diversity and composition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Next, we used WGCNA as a tool to analyze the co-occurrence network of bacterial species within the microbiome of the different surfaces. WGCNA was coopted before for similar purposes [27][28][29]. The implementation of WGCNA in this study allowed us to obtain, for the first time, succession signatures of the plastisphere bacteria at the genus and species levels and to understand their relationship to the surface type and time-point.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we used WGCNA as a tool to analyze the co-occurrence network of bacterial species within the microbiome of the different surfaces. WGCNA was coopted before for similar purposes [27][28][29]. The implementation of WGCNA in this study allowed us to obtain, for the first time, succession signatures of the plastisphere bacteria at the genus and species levels and to understand their relationship to the surface type and time-point.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Halobacterota has sulfate allosteric reduction genes involved in the sulfur cycle, and some genes participate in the carbon cycle, such as those of the order Methanomicrobiales [39,40]. Crenarchaeota has been reported as the major archaeal phylum in both Antarctic and Arctic archaeal studies [41,42], and it was also the major archaeal phylum in previous Svalbard archaeal studies [34]. This is a diverse and widespread phylum that is mainly characterized by acidophilic, thermophilic, and anaerobic properties [43].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the differences in hub archaea in XHX3.3 may be caused by the significantly high NH 4 + concentration at this site. Woesearchaeales are anaerobic archaea from the phylum Nanoarchaeota and are widely distributed in the environment, such as in Antarctic soils [41], trench sediments [73], sewage [74], and cows [75]. It has been shown that Woesearchaeales has positive correlations with Methanoregula and Methanosarcina, which have symbiotic or parasitic relationships with methanogens [24,74].…”
Section: Discussionmentioning
confidence: 99%